EFFECTS OF FULL-FAT CANOLA SEED WITH AN EXOGENOUS ENZYME SUPPLEMENTATION ON PERFORMANCE, CARCASS CHARACTERISTICS AND THYROID HORMONES OF BROILER CHICKENS - V. Rezaeipour; A. Agharajabi; S. Ghareveisi; M. Norozi (Journal of Animal and Plant Sciences, 2015)
This research was performed to determine the effects of full-fat canola seed with enzyme supplementation on performance, carcass characteristics and thyroid hormones (T3 and T4) in broiler chickens. Two hundred and forty one_day-old chicks (ROSS 308) were used in a 2×4 factorial design with three replicates per each treatment. Treatments were 2 levels of enzyme supplementation (0 and 5 g/kg of diet) and 4 inclusion rates of full-fat canola seed (0, 30, 60 and 90 g/kg of diet). The results showed improved (P<0.05) broiler performance by inclusion of full-fat canola seed. Linear improvement was noted in feed conversion ratio (P<0.05) with an increase in dietary levels of canola seed. However, effect of enzyme supplementation on growth performance was not significant (P>0.05). Carcass characteristics, except for liver and pancreas percentage, did not influence by either full-fat canola seed levels or enzyme supplementation. The results of thyroid hormones indicated that use of canola seed, irrespective of enzyme supplementation, in diets changed T3 and T4 concentration at 7 and 42 days of age in broilers. In conclusion, use of full-fat canola seed in broiler diets had positive effect on growth performance.
Keywords: broiler; full-fat canola seed; performance; thyroid hormones